The Link between Overweight/Obesity and Noncommunicable Diseases in Ethiopia: Evidences from Nationwide WHO STEPS Survey 2015 - Bedilu Alamirie Ejigu; Fentanesh Nibret Tiruneh (International Journal of Hypertension)
Background. Noncommunicable diseases (NCDs) are the leading cause of death worldwide. Each year, 15 million adults die from NCDs; more than 85% of these premature deaths occur in low- and middle-income nations. Evidence indicates that overweight and obesity are the main risk factors for NCDs. Although the literature indicates that the burden of NCDs is increasing in Ethiopia, no research has been conducted to demonstrate a link between overweight/obesity and NCDs. Therefore, the aim of this study is to examine the association between overweight/obesity and the common NCDs while adjusting for other important factors. Methods. We analysed data from the 2015 Ethiopia WHO STEPS survey, which was conducted in 2015. A total weighted sample of 9,800 participants (15–69 years) was included. The relationship between nutritional status and NCDs was assessed using bivariate and multivariable logistic regression models while adjusting for covariates. Results. Among the 9,800 participants, 2053 (21% with (95% CI: 19.8–22.1) had hypertension and 1368 (14% with (95% CI: 13.1–15.0) had high cholesterol levels. According to the multivariable logistic regression analysis, being overweight/obese (AOR = 2.0; 95% CI: 1.7–2.3), alcohol consumption, received lifestyle advice, being female, living in urban areas, increased age, having government occupation, and living in SNNP region were positively associated with hypertension. While being underweight (AOR = 0.6; 95% CI: 0.5–0.7), living in the Afar, Somali, and Tigray regions were negatively associated with hypertension. Being overweight/obese (AOR = 1.4; 95% CI: 1.1–1.7), being female, having older age, and living in Somali region were positively associated with a high cholesterol level. Whereas being underweight (AOR = 0.7; 95% CI: 0.6–0.9), received lifestyle advice, reside in rural areas, being farmer, student, and housewife, and living in Gambela region were negatively associated with a high cholesterol level. Conclusion. This study found a statistically positive association between the common NCDs, namely, overweight/obesity, hypertension, and high cholesterol levels. Our findings imply that there is a need for effective interventions to prevent overweight/obesity by encouraging people to increase physical activity, minimize sedentary behavior, and maintain a healthy dietary pattern in order to reduce the risk of hypertension and high cholesterol levels.